Spectrometric identification of organic compounds - Silverstein, Robert M.; Webster, Francis X; Silverstein, Robert M. (New York, John Wiley Sons, 1998)
This book is characterized by its problem--solving approach with extensive reference charts and tables. First published in 1962, this was the first book on the identification of organic compounds using spectroscopy. Now considered a classic, it can be found on the shelf of every Organic Chemist. The key strength of this text is the extensive set of real--data problems in Chapters 8 and 9. Even professional chemists use these spectra as reference data. Spectrometric Identification of Organic Compounds is written by and for organic chemists, and emphasizes the synergistic effect resulting from the interplay of the spectra.
Includes bibliographical references; Index 477-482p.
Keywords: Organic compounds; Spectrometric identification; Chemistry